Melatonin Reduces Inflammation in the Lung Tissue of Type 1 Diabetic Mice Through the ERK/NF-κB Signaling Pathway - Jafar Rezaie; Reza Abbasi; Afshin Rahbarghazi; Mahdi Ahmaadi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2025)
Background. Diabetes is associated with inflammation. In this study, the effect of melatonin on the expression of inflammatory genes and the extracellular signal-related kinase/nuclear factor-kappaB (ERK/NF-κB) signaling pathway was investigated in the lung tissue of type 1 diabetic mice. Methods. Adult male mice weighing 25‒30 g were randomly divided into 4 groups of 10, including control (C), control + melatonin (CM), diabetic (D), and diabetic + melatonin (DM). Streptozotocin (50 mg/kg) was used to induce diabetes. The tumor necrosis factor-alpha (TNF-α) protein level in bronchoalveolar lavage fluid (BALF) was measured by the ELISA test, and the expression of IL-1β, ERK, and NF-κB genes was calculated using the real-time polymerase chain reaction technique. Results. The findings showed that the concentration of the TNF-α protein in the BALF of groups D and DM was significantly higher than that in group C (P<0.001). The amount of this protein in the DM group significantly decreased compared to the D group (P< 0.05). The expression levels of ERK, IL-1β, and NF-κB genes in the lung tissue of the D and DM groups increased significantly compared to the C and CM groups (P< 0.001). However, the expression levels of these genes in the DM group significantly decreased compared to the D group (P< 0.05, P < 0.001, P < 0.01). Conclusion. The results of the present study revealed that melatonin inhibited the expression of inflammatory markers and the ERK/NF-κB signaling pathway in the lung tissue of diabetic mice. Practical Implications. It seems that the induction of diabetes caused an increase in inflammation in the lung tissue of mice, and treatment with melatonin reduced inflammation.